Answer:
Solution: (-4, 2), x= -4 and y =2
Step-by-step explanation:
-8x - y = 30
-2y = x
Substitute for x
-8*(-2y) - y = 30
16y - y = 30
15y = 30
y = 30/15 = 2
Then x = -2y = -2*(2) = -4
Solution: (-4, 2), x= -4 and y =2
Let's solve your equation step-by-step.
2(3x−1)=−6x−2
Step 1: Simplify both sides of the equation.
2(3x−1)=−6x−2
(2)(3x)+(2)(−1)=−6x+−2(Distribute)
6x+−2=−6x+−2
6x−2=−6x−2
Step 2: Add 6x to both sides.
6x−2+6x=−6x−2+6x
12x−2=−2
Step 3: Add 2 to both sides.
12x−2+2=−2+2
12x=0
Step 4: Divide both sides by 12.
12x/12= 0/12
x=0
Answer:
x=0
HOPE THIS HELPS!!! :)
Answer:
D
Step-by-step explanation:
The sum of supplementary angles is 180°
To find the supplement of 60° subtract it from 180°, that is
second angle = 180° - 60° = 120° → D
Answer:
12
Step-by-step explanation:
4s multiples:
4,8,12,16,20,24
6s multiples:
6,12,18,24,30,36
lowest number that is a common multiple between both 4 and 6:
12
You just have to make 36/10 into 3 6/10. After that, it would become 3.6